2008
DOI: 10.1002/jcb.21920
|View full text |Cite
|
Sign up to set email alerts
|

Human head and neck squamous cell carcinoma cells are both targets and effectors for the angiogenic cytokine, VEGF

Abstract: Former vascular endothelial growth factor (VEGF) -head and neck squamous cell carcinoma (HNSCC) studies have focused on VEGF's contributions toward tumor-associated angiogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 45 publications
2
33
0
Order By: Relevance
“…33 VEGF up-regulation has been documented in human cutaneous and head and neck SCCs and is hypothesized to play an important role in their pathogenesis. 34,35 Yet another recently proposed hypothesis is that impaired tyrosine kinase signaling may lead to increased dependence on other tumorigenic factors, such as Ras mutation, and that additional Ras blockade may be necessary to treat tumors that are resistant to tyrosine kinase blockade. Ras mutation in human cutaneous SCCs have been reported, but the prevalence of these mutations are low.…”
Section: Discussionmentioning
confidence: 99%
“…33 VEGF up-regulation has been documented in human cutaneous and head and neck SCCs and is hypothesized to play an important role in their pathogenesis. 34,35 Yet another recently proposed hypothesis is that impaired tyrosine kinase signaling may lead to increased dependence on other tumorigenic factors, such as Ras mutation, and that additional Ras blockade may be necessary to treat tumors that are resistant to tyrosine kinase blockade. Ras mutation in human cutaneous SCCs have been reported, but the prevalence of these mutations are low.…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations, by our lab and others, demonstrated that the angiostatic agent, endostatin, inhibited migration and invasion of HNSCC cells, implying that HNSCC cells share some functional characteristics with endothelial cells [8, 9]. In subsequent studies, we demonstrated that HNSCC cells produce exceptionally high levels of VEGF, express both VEGFR1 and VEGFR2, and proliferate in response to autologously produced VEGF [10]. This autocrine-paracrine VEGF growth loop can promote HNSCC tumorigenesis in a biphasic fashion via its proangiogenic and growth promotion roles [10].…”
Section: Introductionmentioning
confidence: 85%
“…It is prostulated that VEGF targeted therapy has the potential to fulfill both anti-angiogenic and anti-tumorigenic functions (Tong, et al, 2008). As reported, CD44 certainly posseses a valid target for anti-cancer therapy.…”
Section: Associated Targeting Therapymentioning
confidence: 94%